THE ROLE-PLAY APPLICATION AS METHOD OF TEACHING IN SPEAKING ENGLISH TO THE JUNIOR HIGH SCHOOL STUDENTS - Firmansyah, Muhamad Hilman (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
The paper is about “The Role-Play Application as Method of Teaching in Speaking to the Students of Junior High School was proposed to find out to what extent role-play was used in teaching speaking to the students of junior high school and what were obstacles experienced by the teacher when he implemented it in the classroom. English teacher in grade seven students of Islamic Junior High School of MTs Cilawu Garut was the main participant of this research. Qualitative method was applied as the primary scheme by engaging non-participatory observation and interview to gain the data. The result findings presented that the teacher broke principles in teaching speaking and some fundamentals in practicing the role-play. Teachers also found problems such as the bottlenecks to deal with students whose pronunciation ability were poor, especially in pronouncing new words, to manage the noise during the performance of role-play. However, many experts believe that the use of role-play is very essential in communicative language teaching to bring English into the real-life atmosphere and the communicative competence. This study is expected to give contribution to the English teaching mostly in performing role-play teaching methods of teaching. Furthermore, it is recommended for the next researchers to broaden study on the application of role-play out of the speaking domain, but it can also be used in other communicative language teaching aspects.